Soft Skills, the B.Sc. Parallel for a Successful Engineer - Mahmoud, Salameh (Advances in Social Sciences Research Journal, 2017)
This study investigates the most common soft skills engineers should acquire in order to lead a successful career and the KPIs for each skill. The sample of the study is fifteen senior engineers from ten well-known companies in KSA. The data collection tool is interviewing the senior engineers in the sample about the required soft skills and the key performance indicators of each soft skill. The findings of the study showed that there are a number of soft skills that are necessary first to pass an interview and second to survive in your future career. Furthermore, the respondents in the interview agreed upon a group of KPIs (key performance indicators) engineers should have in order to reflect these soft skills. The study recommends that new engineer grads should go through a well -designed training course where they are exposed to authentic examples, videos, recoded materials and probably visits to engineering companies in order to acquire the most common soft skills. Key words: KPI, soft skills, frequency of KPIs, senior engineers, new engineer grads